2018
DOI: 10.1016/j.compedu.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of internationalised versus local content on online intercultural collaboration in groups: A randomised control trial study in a statistics course

Abstract: The influence of internationalised versus local content on online intercultural collaboration in groups: A randomised control trial study in a statistics course. Computers & Education, 118 pp. 82-95. For guidance on citations see FAQs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 61 publications
2
36
0
Order By: Relevance
“…Considering the students' experiences using digital learning platforms, the strategies, guidelines or models presented, and the types of learning approaches, four categories were constructed -(i) Student Experiences; (ii) Strategies and Models; (iii) Blended Learning; and (iv) MOOC -as presented in Table 3. GEMMELL et al, 2015;HARRISON et al, 2018;HYETT et al, 2018;MITTELMEIER et al, 2017;POUROMID, 2019;STANWAY et al, 2019;WIHLBORG et al, 2017). (ALTINAY et al, 2019;HOWARD et al, 2017;KENT et al, 2017;KUNG, 2017;MORONG;DESBIENS, 2016).…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Considering the students' experiences using digital learning platforms, the strategies, guidelines or models presented, and the types of learning approaches, four categories were constructed -(i) Student Experiences; (ii) Strategies and Models; (iii) Blended Learning; and (iv) MOOC -as presented in Table 3. GEMMELL et al, 2015;HARRISON et al, 2018;HYETT et al, 2018;MITTELMEIER et al, 2017;POUROMID, 2019;STANWAY et al, 2019;WIHLBORG et al, 2017). (ALTINAY et al, 2019;HOWARD et al, 2017;KENT et al, 2017;KUNG, 2017;MORONG;DESBIENS, 2016).…”
Section: Analysis Of Resultsmentioning
confidence: 99%
“…Further, we found several factors influenced students' perspectives towards curriculum internationalisation (including perceived personal English language proficiency, previous international experiences, and educational background) (RQ2), meaning internationalisation experiences are not 'one size fits all' and may be experienced differently by students from different backgrounds. For this reason, steps should be taken to make internationalisation relevant to students' own lives (Mittelmeier et al, 2018) and authentically engage with perspectives of home students (Harrison, 2015;Sandström & Hudson, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…• is intended to act as a springboard to developing skills around intercultural interaction.' Growing evidence has outlined internationalised academic content can benefit students' overall HE experience by developing intercultural competencies (Trahar & Hyland, 2011), encouraging interaction between peers from different backgrounds (Arkoudis et al, 2013) and supporting engagement and participation (Mittelmeier, Rienties, Tempelaar, Hillaire, & Whitelock, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Familiarity with the topic of the data can create confidence and ground critical thinking. For example, Mittelmeier et al (2018) report use of open data from the World Bank in a learning activity and found that the use of locally-relevant content (country-level educational statistics) encouraged greater participation in intercultural student collaborations.…”
Section: Pedagogical Connectionsmentioning
confidence: 99%
“…This provide avenues to inform next steps in research and practice. To highlight two such links: research evidence suggests that relevance can improve educational outcomes (Mittelmeier et al 2018;Cordova and Lepper 1996). Authentic learning research (e.g.…”
Section: Why Would Educators Make Use Of Open Data In Their Teaching?mentioning
confidence: 99%